2019 Novel Coronavirus Disease (Covid-19): Detection and Diagnosis System Using IoT Based Smart Glasses - M. N. Mohammed, Nurul Aslamiah Hazairin, Halim Syamsudin, S. Al-Zubaidi, Sairah A.K., Safinaz Mustapha, Eddy Yusuf (International Journal of Advanced Science and Technology, 2020)
The most recent pneumonia outbreak caused by a novel coronavirus (COVID- 19) in China is posing a great threat and declared a global public health emergency. This disease was firstly discovered in Wuhan, China, on December 2019 and spread to the world until now. Nowadays, infrared thermometers are being used everywhere to check the body temperature in places with large number of people. But this action is not really effective even it might cause the spread of the coronavirus from the infectious people to the person who does the screening process. In order to solve this issue, the fast and precise identification of coronavirus is needed. The aim of this study is to design a system that has capability to detect the coronavirus automatically from the thermal image fast with less human interactions using IoT based smart glasses technology. Furthermore, the proposed design has capability to perform face detection on suspected case of Covid-19 among crowds who has high body temperature. The design will add information of the visited location of the suspected carriers of the virus through Google Location History (GLH) to provide reliable data on the detection process.